Northern Bobwhite Response to Control of Red Imported Fire Ants in the Gulf Coast Prairie of Texas - Kelly M Redmond; Eric D Grahmann; Fidel Hernández; Leonard A Brennan; Michael E Morrow; Timothy Anderson (National Quail Symposium Proceedings, 2022)
The population decline of northern bobwhite (Colinus virginianus; hereafter, bobwhite) on the Texas Gulf Coast Prairie, USA is largely attributed to habitat loss. However, red imported fire ants (Solenopsis invicta) occur throughout the region and are considered a possible contributing factor to the bobwhite decline. The objectives of our study were to determine the influence of red imported fire ants on bobwhites by comparing bobwhite nest success, survival, and density between sites treated with fire ant bait (treatment) and reference (control) sites. Our study was conducted on 3 private ranches in Goliad and Refugio counties, Texas. Each ranch contained 2 paired experimental units that consisted of a treatment and control site (500 ha each). The treatment sites received an aerial application of fire ant bait (Extinguish® Plus) during April 2018, whereas the control sites were not treated. We estimated mound density by counting fire ant mounds using distance sampling. We used radio-telemetry to monitor bobwhite nest success and survival, and we estimated bobwhite densities using distance sampling via helicopter surveys. Fire ant mound density decreased through time on both treatment and control sites. However, fire ant mound density was lower on treatment sites than control sites, indicating the insecticide was effective at decreasing fire ant mound density. Bobwhite survival, nest success, and density did not statistically differ between control and treated sites either pre-treatment (2017) or post-treatment (2018), but survival and nest success metrics were numerically higher in treated units. Bobwhite survival remained relatively stable in the treatment units 4 weeks after application but decreased in the control units. Following treatment, apparent nest success in the treated units increased by 37.4% while nest success in the control units decreased by 35.2%. Bobwhite populations were low in this ecoregion, which influenced our ability to trap and monitor many bobwhites or monitor many nests. In addition, it may be possible that repeated, annual treatments for fire ants are necessary for a benefit to accrue and be observed in bobwhites. Our results indicate that there may be potential benefits to bobwhites from fire ant reduction that deserve further research attention.
Keywords: Colinus virginianus; Extinguish Plus; hydramethylnon; northern bobwhite; red imported fire ant; Solenopsis invicta; Texas